Estudo da substituição de agregados miúdos naturais por pó de pedra em concreto de cimento portland - Duarte, João Batista (2013)
The sharp consumption of natural resources by the construction industry has motivated numerous studies concerning the application of waste to replace partially or fully, some materials, such as aggregates, thereby reducing the environmental impact caused by the extraction of sand and crushing process. The application of stone dust from crushing process arising as an aggregate for the production of Portland cement concrete is a viable alternative in view of the high cost of natural sands, in addition to the environmental damage which causes its operation to the environment. The stone dust has reduced cost compared to natural sand because it is produced in the beds of their own quarries, which are usually located close to major urban centers. This study examined the feasibility of using stone dust from the crushing of rock gneisses in the state of Bahia, replacing natural quartz sand. In the development of scientific study was conducted to characterize physical and chemical raw materials applied and molded cylindrical specimens , using as reference values Fck 20, Fck 25 and Fck 30 MPa ( resistance characteristic of the concrete after 28 days) in following compositions stone powder: 10%, 30%, 50 %, 100% and 100% with additive. The specimens were cured and subjected to the tests of compressive strength and water absorption, then the samples were subjected to the tests of X-ray diffraction and scanning electron microscopy. The results obtained showed that the composition with 10% stone powder showed the best results regarding the physical and mechanical tests performed, confirming the reduction in compressive strength and increased water uptake increased as the content of the powder stone in the concrete composition